GENDER DIFFERENCES IN LEADERSHIP - Mohamad Azmi Adnan; Muhammad Afif Shahmie Bin Mohd Shah (Jurnal Academia Praja, 2019)
Gender differences have always been debated in a lot of platforms including in universities. In universities, both female and male leaders are being proactive with their advocacies in their own leadership pursuits in which at the same time they have to focus on their academic performances as well. Some questions may arise: how do they handle both of these pursuits at the same time? Will they portray any differences in balancing of these pursuits? Research has proven that gender differences do exist between male and female leaders especially in the aspect of leadership, academic performances and the ability of them to do multi-tasking and interestingly, this particular research has been in the favour of female leaders.In this research paper, gender differences will be determined between male leaders of Jawatankuasa Perwakilan Kolej Delima and female leaders of Jawatankuasa Perwakilan Kolej Melati, in which both of these organisations are recognized as the most victorious organisations of all residential colleges in UiTM Shah Alam. A quantitative method has been applied in the commission of this research whereby it requires 34 respondents from both organisations to answer a questionnaire. From this research, it has been found that even though prior research made by the previous researchers was in the favour of female leaders, but, male leaders of Jawatankuasa Perwakilan Kolej Delima tend to show that they could create equilibrium in both of the pursuits that they have involved in, compared to female leaders of Jawatankuasa Perwakilan Kolej Melati. A qualitative method in the form of interview also has been conducted in order to obtain thorough insights of what have been transpired by all of them in pursuing both of the pursuits. Albeit of the disparities, all of the respondents share the same attributes in which they are persevere, brave, courageous and strong to find equilibrium between both of the pursuit as their interpretation of being a victorious leader is being a survivor, not a quitter. All in all, both female and male leaders of respondents are in the pursuit of being a victorious leader as the definition of „victorious leader‟ for them are being a survivior in facing all of the ruthless and dreadful challenges of being a leader.